PENGELOLAAN PUSAT SUMBER BELAJAR PADA PUSDIKLAT SDM KESEHATAN DEPARTEMEN KESEHATAN REPUBLIK INDONESIA (Jurnal Teknodik, 2018)
The aim of this research is to explore the possibility for managing Learning Resource Center of Pusdiklat Departmen Kesehatan more effectively. Descriptive analytic method is used in this research. Data Collection are collected through in-depth interview, observation, and document analysis. Those data are then analyzed through several steps such as data reduction, data presentation, conclusion, and verification. Result of this study indicated that the management Learning Resources Center is not adequate to be viewed from theconcept of managementt. The human resources of the center are not adequate in quantity as well as professional quality. The facilities of the center are not adequate to support the intended activities. The lack of budgetary allocation is also hampering the effectiveness of the center operation.
Keywords: Management; learning; learning resources; learning resource centers; learning resources center